Faktor Penghambat Adopsi Mobile Banking Pada Generasi Milenial Mahasiswa Universitas Mulawarman - Dimas Adha Septyan (Inovbiz: Jurnal Inovasi Bisnis, 2020)
The world today is driven by an instant and easy lifestyle. This can be seen from the development of digital-based information technology so that information can be managed in real-time without human assistance by using an automated and sophisticated system. In this case, M-Banking can assist in accessing banking information and services quickly and easily. M-Banking users in the millennial generation of Mulawarman University are low. Therefore, the aim of this study is to analyze the barriers that prevent the millennial generation of Mulawarman University from adopting M-Banking by implementing Innovation Resistance Theory (IRT). This study uses a quantitative method approach through filling out a questionnaire online involving 155 millennial generation respondents at Mulawarman University to empirically test the innovation resilience model. The results showed that of the six barriers studied, value barriers, traditional barriers and image barriers had a negative effect on adoption intentions. This journal contributes by applying less learned perspectives through innovation resistance theory to assist banks in a deeper understanding of consumer behavior and perceptions and helping banks to develop solutions to increase the adoption rate of M-Banking itself.